Characterization of Kuala Rompin clay (KRC) and empty fruit bunch ash (EFBA) for potential application in the formulation of geopolymer cement - Money, Barima; Siti Qurratu’ Aini, Mahat; Norasyikin, Ismail; Modather, Rayan Hassan; Abutu, David; Nyah, Francis; Umunnawuike, Chika; Nwaichi, Peter Ikechukwu; Agi, Augustine Aja (Springer Nature, 2025)
The growing environmental concerns associated with conventional Portland cement production have sparked increased interest in sustainable alternatives, such as geopolymer binders. This study explores the formulation and performance of an innovative clay-based geopolymer cement synthesized from Kuala Rompin clay and potassium hydroxide derived from Empty Fruit Bunch Ash (EFBA), a readily available agricultural waste. The geopolymer matrix was further enhanced using bauxite, magnesium, and sodium silicate as functional additives to improve reactivity and durability. Extensive characterization of the raw materials, conducted through X-Ray Fluorescence, X-ray Diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy, Energy-Dispersive X-ray Analysis, Brunauer-Emmett Teller, particle size distribution, and Thermogravimetric Analysis (TGA), confirmed their chemical and structural suitability for geopolymerization. The XRD results show the presence of hatrurite, quartz, calcine, and potassium in the geopolymer cement. Also, the FTIR results reveal the presence of an aluminosilicate gel network (K-A-S-H). Therefore, this research will contribute significantly in transforming low-cost, locally sourced materials and biomass waste into a high-performance, low-carbon cement alternative, promoting circular economic principles and contributing to the global effort to decarbonize the construction and oil and gas sectors.